Potential for anticoagulant therapy in the most vulnerable groups of patients - Irina A. Zolotovskaya; Victoria D. Sabanova; Igor L. Davydkin (Российский кардиологический журнал, 2022)
Patients with atrial fibrillation (AF) often have comorbidities or characteristics (senile age, chronic kidney disease, high risk of coronary events, cognitive impairment) that can affect the patient's prognosis and that must be taken into account when prescribing therapy for stroke prevention. However, there are groups of patients with a high risk of bleeding, which cause concern to the doctor about possible hemorrhagic events. Direct Oral Anticoagulant (DOAC) Xarelto® (rivaroxaban) compared with other DOACs confirmed a favorable safety profile in the widest patient population: from children to senile patients. Moreover, high safety indicators in the treatment with rivaroxaban were obtained in vulnerable, from the point of view of hemorrhagic risks, patients with AF with various risk factors: those with a high risk of bleeding according to HAS-BLED scores, elderly patients, patients with chronic kidney disease, including advanced stages, as well as with anemia. It is important to remember that bleeding is not the only undesirable outcome for an elderly patient with AF. To ensure the most favorable prognosis of his life and health, it is necessary to level the maximum possible number of risks. The use of rivaroxaban may make it possible to approach the therapy of an elderly patient with AF in a comprehensive manner: to prevent stroke with a proven safety profile, while simultaneously reducing the risks of coronary events and renal complications, as well as contributing to the formation of high adherence — a necessary condition for obtaining the expected results of therapy.